2021
DOI: 10.1186/s40842-021-00131-w
|View full text |Cite
|
Sign up to set email alerts
|

The association between Helicobacter pylori and obesity: a systematic review and meta-analysis of case–control studies

Abstract: Introduction The relationship between H. pylori infection and obesity development has remained controversial among various studies. The aim of this study was to clarify the pooled effect of H. pylori infection on the development of obesity and vice versa. Methods We searched international databases including Medline (PubMed), Web of sciences, Scopus, EMBASE, Cochrane, Ovid, and CINHAL to retrieve all case–control studies reporting the effect of H. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 40 publications
1
25
0
1
Order By: Relevance
“…A systematic review enrolling studies performed in 62 countries from 1970 to 2016 showed a 48.5% prevalence of H. pylori infection; based on regional prevalence estimates, by 2015 4.4 billion individuals were believed to be infected worldwide (9) . A recent Cochrane review reported a mean prevalence of H. pylori infection of 53.7% was reported, and according to another study, the mean prevalence in Brazil was 71.2% (10)(11)(12)(13)(14) .…”
Section: Discussionmentioning
confidence: 98%
“…A systematic review enrolling studies performed in 62 countries from 1970 to 2016 showed a 48.5% prevalence of H. pylori infection; based on regional prevalence estimates, by 2015 4.4 billion individuals were believed to be infected worldwide (9) . A recent Cochrane review reported a mean prevalence of H. pylori infection of 53.7% was reported, and according to another study, the mean prevalence in Brazil was 71.2% (10)(11)(12)(13)(14) .…”
Section: Discussionmentioning
confidence: 98%
“…Among specific microorganisms, Helicobacter pylori is studied for its Research, Society andDevelopment, v. 11, n. 4, e11411427153, 2022 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v11i4.27153 possible correlation with leptin and ghrelin. Furthermore, it shows more frequently in obese individuals than in individuals with healthy BMI (Baradaran et al, 2021;Endalifer & Diress, 2020).…”
Section: Obesity Mechanismsmentioning
confidence: 99%
“…Conversely, obesity can occur as a result of infection (Pasarica and Dhurandhar, 2007;Dhurandhar, 2011), and infection-induced chronic low-grade inflammation may lead to insulin resistance (Fernández-Real et al, 2006), suggesting bi-directional interactions between infection and metabolic disorders. Furthermore, several pathogens, such as HSV, CMV, H. pylori, and P. gingivalis, are implicated in both metabolic disorders and AD (Jeon et al, 2012;Harris and Harris, 2015;Fleck-Derderian et al, 2017;Beydoun et al, 2018;Lövheim et al, 2018;Mei et al, 2020;Baradaran et al, 2021;Costa et al, 2021;Salem et al, 2021), supporting the potential mechanistic link between infection, MetS, and dementia etiology.…”
Section: Insulin and Leptin Mediating The Link Between Infection And Neurodegenerative Disorders Infectious Etiology Of Dementiamentioning
confidence: 99%